Adsorption of Mn(II) in aqueous solution using Fe oxide and Mn oxide-coated sand - Aganon, Mannie C. (2012)
The application of manganese and iron oxides in groundwater treatment is not fully explored and is limited because of the difficulties in separation from the aqueous phase. In this paper, the sorption properties for Mn(II) of immobilized Mn-oxide and Fe-oxide adsorbents namely Manganese Oxide-coated Sand1 (MOCS1), Manganese Oxide-coated Sand2 (MOCS2), Iron Oxide-coated Sand1 (IOCS1), Iron Oxide-coated Sand2 (IOCS2), and Manganese & Iron Oxide-coated Sand (MIOCS) were investigated. Characterization of the adsorbents showed distinct amounts and types of oxide in their coating. The equilibrium capacities (25 deg.C) fitted well both the Freundlich and Langmuir isotherms, indicating surface heterogeneity and a monolayer adsorption in all the adsorbents. The Equilibrium capacities increased with pH (5.5-8) and with temperature (24-45 deg.C), and were consistent with the Langmuir model to be in the order of MIOCS>MOCS1>MOCS2>IOCS2>IOCS1. Kinetic data showed high correlation with the pseudo-second order model in all temperatures (25-45 deg.C) signifying a chemisorption controlled mechanism in all adsorbents. The activation energies (Ea) activation Parameters (AG*, AH*, AS*) and thermodynamic parameters (AGo, AHo, ASo) confirmed that adsorption with MIOCS was endothermic and more spontaneous at higher temperature while that with the other adsorbents was the opposite. Also the thermodynamic study showed that the process involved the formation of an activated complex, with MOCS1 and MIOCS follow3ing a physical-chemical mechanism, and with the rest of the adsorbents following a purely chemical mechanism. Finally, the applicability of MIOCS and IOCS2 in dilute concentrations of MN2+ and FE2+ was explored (0.5ppm Mn2+, 0.5ppm FE2+). Both were found to be effective in reducing MN2+ concentration to below 0.025ppm with capacities that were higher in the presence of suspended iron and manganese oxides. The adsorbents are viable for in-plant and at point-of-use treatment of groundwater.
"April 2012."
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Adsorption; Groundwater -- Purification; Manganese oxides; Iron oxides; Aqueous solutions